SOSIALISASI ANTIBULLYING DI LINGKUNGAN MADRASAH IBTIDAIYAH DESA POPOH SIDOARJO - Milah, Ima Datul; Karyadi, Tanzylla Azzaranur; Azira, Nurkaira; Khairil, Ahmad Syahrul; Maulana, Firman Ali (Indonesian Journal of Engagement, Community Services, Empowerment and Development, 2025)
This study addresses the phenomenon of bullying at Madrasah Ibtidaiyah (MI) in Desa Popoh, Wonoayu Sub-district, Sidoarjo Regency, which is a serious problem in elementary school environments that negatively affect students psychologically, academically, and socially. The study aims to improve students' understanding of bullying through an anti-bullying socialization program. The method used is a qualitative approach with Participatory Action Research (PAR) involving 10 students from grades 4-6 through educational materials and role-playing activities. Data were analyzed quantitatively from pre-test and post-test results and student participation observations. The main findings indicate an 80% increase in student understanding of bullying and 70% active participation, alongside a decrease in bullying case reports at school. The conclusion emphasizes the need to develop programs involving teachers, parents, and the school environment to foster an anti-bullying culture and safe, positive learning environment.